Gallbladder cancer according to its histological type and TNM staging, Arequipa, Perú - Gamarra Manrique, Renzo Reynaldo (2012)
Introduction: Gallbladder cancer is increasing in specific ethnic groups such as the native American. The use of the TNM staging is a useful approach to design appropriate treatment and predict a reliable survival in patients. Objectives: To determine the histológico type of gallbladder cancer and the staging of presentation according to the classification TNM. Material and Methods: This was across-sectional and analytical study. Assessed 73 patients with diagnosis of gallbladder cancer histopathological, which determines the histological type more frequent and belonging to a stage of the TNM classification. The study was realized in the Hospital Honorio Delgado of Arequipa, Perú, the temporary period January 2005 to June 2010. Results: The most frequent histological type was adenocarcinoma 71.2%. The most common histological subtype was tubular adenocarcinoma with 42.3% of cases. The TNM stage more frequent was the IIB with 35.5% of cases, followed by the IV with 24.6%. Conclusion: In Hospital Honorio Delgado of Arequipa histological type of gallbladder cancer more frequent among the years 2005 - 2010 is tubular adenocarcinoma. Also the patients showed at the time of the diagnosis in stage IIB with greater frequency.